2018
DOI: 10.1177/0042098018787738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the local employment impacts of enterprise zones: A critique

Abstract: Enterprise zone policy is a potential tool for the regeneration of distressed areas, based primarily on tax incentives to businesses locating in the target areas. The tool has been tested in several countries over more than 35 years but there is no consensus on whether or not it is effective and efficient in creating jobs and reducing unemployment in targeted localities. This paper reviews seminal enterprise zone evaluations in the UK, USA and France. More than one-half of the studies reported local employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(155 reference statements)
1
4
0
Order By: Relevance
“…That means, assuming that most of these firm would have invested there anyway, the government would have allocated almost 7.7 billion PLN more for labour policy spending. These results go along with the conclusions of Chaudhary and Potter (2018) that the UK and the US EZs' cost per job created was between 8 000 and 20 000 USD per annum in 2016 prices.…”
Section: Unemploymentsupporting
confidence: 74%
See 3 more Smart Citations
“…That means, assuming that most of these firm would have invested there anyway, the government would have allocated almost 7.7 billion PLN more for labour policy spending. These results go along with the conclusions of Chaudhary and Potter (2018) that the UK and the US EZs' cost per job created was between 8 000 and 20 000 USD per annum in 2016 prices.…”
Section: Unemploymentsupporting
confidence: 74%
“…Third, this paper extends the research of Chaudhary and Potter (2018), where seminal enterprise zone evaluations in the UK, USA and France were conducted. After a review of literature on Polish SEZs, the author confirms that typically narrow-focused research designs and a theoretical evaluation have contributed to the lack of consensus and policy insight, potentially exacerbated by non-exact data.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Previous research has shown that 41% of the 58,000 jobs created in enterprise zones were relocated from elsewhere. Over half of jobs on UK enterprise zones between 1981 and 1993 were attributable to displacement and deadweight, usually from nearby high unemployment areas (Chaudhary and Potter, 2019). Swinney (2019) notes in reviewing the subsequent wave of enterprise zones designated by a later government in the 2010s, that at least a third of jobs were displaced from elsewhere, that the total number of new jobs was only a quarter of the number estimated by the Treasury in 2011, and that most jobs created were low-skilled.…”
Section: Resultsmentioning
confidence: 99%